2016
DOI: 10.1182/blood-2016-01-688796
|View full text |Cite
|
Sign up to set email alerts
|

The BCL2 selective inhibitor venetoclax induces rapid onset apoptosis of CLL cells in patients via a TP53-independent mechanism

Abstract: • Venetoclax potently induces rapid onset apoptosis of CLL cells in vitro and in vivo, independently of TP53 function.• Objective responses in patients with del(17p) and/or TP53-mutated CLL are as deep as patients with no perturbation of TP53.BCL2 blunts activation of the mitochondrial pathway to apoptosis, and high-level expression is required for chronic lymphocytic leukemia (CLL) survival. Venetoclax (ABT-199) is a small-molecule selective inhibitor of BCL2 currently in clinical trials for CLL and other mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
228
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(246 citation statements)
references
References 36 publications
14
228
0
4
Order By: Relevance
“…In contrast, venetoclax (ABT-199), another selective inhibitor of BCL2, was not associated with thrombocytopenia. 22 Several studies have already demonstrated the clinical benefit of venetoclax in relapsing chronic lymphocytic leukemia patients, whereas studies in patients with DLBCL are still ongoing. 23 Several agents aimed at modulating MYC expression or activity are presently undergoing clinical development.…”
Section: Strategies For Refractory Patientsmentioning
confidence: 99%
“…In contrast, venetoclax (ABT-199), another selective inhibitor of BCL2, was not associated with thrombocytopenia. 22 Several studies have already demonstrated the clinical benefit of venetoclax in relapsing chronic lymphocytic leukemia patients, whereas studies in patients with DLBCL are still ongoing. 23 Several agents aimed at modulating MYC expression or activity are presently undergoing clinical development.…”
Section: Strategies For Refractory Patientsmentioning
confidence: 99%
“…The clinical responses of CLL patients were also independent of del17p, TP53 mutation, and TP53 function. 39 Recently, a phase II, open label, two-arm study reported the outcome of venetoclax monotherapy in 64 CLL patients who relapsed after, or were refractory to, ibrutinib or idelalisib, of whom 43 were on prior ibrutinib (Arm A) and 21 (Arm B) on prior idelalisib. ORR by an independent review for Arm A and Arm B was 70% and 48%, respectively.…”
Section: The Development Of Venetoclax As Monochemotherapymentioning
confidence: 99%
“…Venetoclax specifically binds and inhibits Bcl-2, releasing BH3 proteins to activate Bax and/or Bak and cause mitochondrial outer membrane permeabilization. [8][9][10] Venetoclax has been recently approved for previously treated CLL patients. 9 However, despite an overall response rate of 71% to 79%, the complete remissions rate for venetoclax monotherapy was relatively low (20%).…”
Section: Introductionmentioning
confidence: 99%